La croix et les idoles d’ après l’ Apologie d’ Athanase ‘Contre les païens’ - Franco Beatrice, Pier (Antigüedad y Cristianismo, 1990)
Through the analysis of some significant passages of Athanasius’ apology «Against the Pagans on the Incarnation of the Word», and also thanks to their comparison with other selected texts by the same author, P. F. Beatrice tries to date this still problematic work to around the middle of the fourth century. In particular, he intends to show that Athanasius did know the Neoplatonic philosophy of his time sufficiently well and that the target of his polemic was especially Porphyry. But anti-pagan criticism also supplies Athanasius with a substantial support in his struggle with the Arian heresy which had been shared by his great precursor and adversary Eusebius of Caesarea.